2004
DOI: 10.1023/b:joec.0000042072.18151.6f
|View full text |Cite
|
Sign up to set email alerts
|

Field-Testing of Methyl Salicylate for Recruitment and Retention of Beneficial Insects in Grapes and Hops

Abstract: Evidence for recruitment and retention of beneficial insects in grapes and hops using controlled-release dispensers of methyl salicylate (MeSA), a component of herbivore-induced volatile blends, is presented. In a replicated experiment conducted in a juice grape vineyard, sticky cards in blocks baited with MeSA captured significantly greater numbers of five species of predatory insects (Chrysopa nigricornis, Hemerobius sp., Deraeocoris brevis, Stethorus punctum picipes, Orius tristicolor) than unbaited blocks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
184
3
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(197 citation statements)
references
References 8 publications
7
184
3
3
Order By: Relevance
“…Thaler (1999) also reported increases in parasitism of S. exigua on induced plants versus controls. A series of field studies demonstrated that sachets of individual synthetic HIPVs could be used to attract and retain natural enemies in perennial crop systems (James 2003a,b;James and Price 2004;James and Grasswitz 2005). In particular, these studies showed that (Z)-3-hexenyl acetate, farnesene, and methyl salicylate could be used to manipulate behavior of beneficial insects under field conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thaler (1999) also reported increases in parasitism of S. exigua on induced plants versus controls. A series of field studies demonstrated that sachets of individual synthetic HIPVs could be used to attract and retain natural enemies in perennial crop systems (James 2003a,b;James and Price 2004;James and Grasswitz 2005). In particular, these studies showed that (Z)-3-hexenyl acetate, farnesene, and methyl salicylate could be used to manipulate behavior of beneficial insects under field conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Exploitation of chemical signaling by plants that attract natural enemies has potential for enhancing biological control in agroecosystems (Hunter 2002). For example, synthetic herbivore-induced plant volatiles (HIPVs) have been used to attract and retain beneficial insects into vineyards and hopyards (James 2003a(James ,b, 2005, which has led to a reduction in pest densities (James and Price 2004;James and Grasswitz 2005). To date, however, little is known about practical application of HIPVs in cotton agroecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of methyl salicylate in our sample is worth mentioning, as this compound has been reported to play an important role in the attraction of herbivore enemies (James and Price, 2004;Zhu and Park, 2005).…”
Section: Discussionmentioning
confidence: 77%
“…That a general attraction of natural enemies into a field can result in significant reduction of herbivore numbers is also evident from studies in which synthetic attractants that were released from dispensers in crop fields increased the numbers of natural enemies and reduced pest numbers [39]. Methyl salicylate is one of the compounds that seems to be of particular importance in mediating attraction of several natural enemies [4,[39][40][41], some other likely candidates for manipulation are discussed below. Continuous releases might also be the most effective means of repelling herbivores and to prime for plant defences.…”
Section: Priming For Enhanced Plant Defence As An Additional Benefitmentioning
confidence: 95%
“…This compound has been shown to induce both direct defence against aphids and the production of the aphid repellent 6-methyl-5-hepten-2-one, the key attractant for an important aphid parasitoid. Methyl salicylate is another compound that can be expected to play an important role in plant-plant communication, and in repelling herbivores and attracting beneficial arthropods [4,40,41,48]. But overall, there is still a major need to improve our knowledge of what compounds are of key importance [43 ,49,50].…”
Section: Which Signals To Target?mentioning
confidence: 99%